Clinically Important Yersinia: Minireview - Dheyab, Zaid Sahib (Jour Med Resh and Health Sci, 2022)
Yersinia spp. is an enterobacteria that causes a prominent zoonotic diseases. Plague, Yersinosis, Far-East Scarlett-Like Fever and Kawasaki Disease were a common recorded diseases. While Yersinia genus compile 18 species, only three were clinically important human pathogens: Y. pseudotuberculosis, Y. pestis and Y. enterocolitica. Serotyping is common among Yersinia and used to distinguish between pathogenic and non-pathogenic species. Clinical symptoms ranged from high fever (up to 39 to 40°C), malaise, chills, and headache in Plaque to gastrointestinal symptoms usually resolve within 2 to 3 weeks. The complications may include, erythema nodosum, arthritis, Reiter’s disease and glomerulonephritis, can occur. Y. enterocolitica and Y. pseudotuberculosis may associate with mesenteric lymphadenitis, terminal ileitis, pseudo-appendicitis and sepsis. Manipulation of Yersinia may require biosafety level 3 laboratory and all immunological, and molecular assay targeting F1 antigen for diagnosis. Yersinia have arrays of virulence factors includes: Ypm (responsible for superantigen symptoms), pYV(plasimd who carry set of virulence genes: Yops, outermwmbrane proteins; YadA, an adhesin who binds to collagen and laminin and eliciting inlafamatiry respones), HPI (The high-pathogenicity island which carry: Psn, an receptor for the siderophore; irp1 and irp2 which encode high-molecular-weight proteins involved in synthesis of yersiniabactin) and Yersinia Chromosomal Virulence Factors (YCVF):(i) invA, encoding an invasin, (ii) ail, encoding a protein that mediates adhesion and invasion into host cells, and (iii) ystA or ystB, encoding enterotoxins that cause fluid accumulation in the intestines. The drug of choice are Streptomycin and gentamicin while many MDR isolates were reported worldwide and there is an relation between resistance style and serotypes of Yersinia. The current review conclude importance of Yersinia spp. as a zoonotic pathogen equipped with group of virulence traits and resistance to antibiotics that may push a real threat for infected person.